Two new frog species (Microhylidae: Cophixalus) from the Australian Wet Tropics region, and redescription of Cophixalus ornatus - Hoskin, Conrad J. (Zootaxa, 2012)
In Australia the frog family Microhylidae is largely restricted to tropical rainforests of the Wet Tropics region in the north-east of the country, but in that region the family is diverse. Only one species, Cophixalus ornatus, is widespread in the WetTropics but there has been suspicion that it may comprise multiple species. A recent study (Hoskin et al. 2011) assessedgenetic and phenotypic variation across the range of C. ornatus, finding three deeply divergent genetic lineages that differin mating call and some aspects of morphology. Two of these lineages abutt in the central Wet Tropics and in that areahybridization was found to be very limited despite sympatry at high densities. Based on multiple lines of data, Hoskin etal. (2011) concluded that the three genetic lineages represent biological species. The taxonomy of these three lineages isresolved here. I describe two new species, Cophixalus australis sp. nov. and Cophixalus hinchinbrookensis sp. nov., andredescribe C. ornatus. The three species are not distinguishable based on any single morphological or call trait and arebest identified by genetics or locality. The distributions of the three species are largely allopatric. Cophixalus ornatus isfound in rainforest in the northern Wet Tropics, C. australis sp. nov. occurs in rainforest and adjacent wet sclerophyllforests in the central and southern Wet Tropics, and C. hinchinbrookensis sp. nov. inhabits rainforest and montane heathon Hinchinbrook Island. All three species are common. Cophixalus australis sp. nov. contains three genetic subgroupsthat are considered a single species based on phenotypic similarity and high levels of hybridization at contact zones. Thedescription of Cophixalus australis sp. nov. and Cophixalus hinchinbrookensis sp. nov. brings the number of Australian Cophixalus species to 18, 15 of which are restricted to the Wet Tropics region.